Maternal Thyroid Dysfunction and Gestational Anemia Risk: Meta-Analysis and New Data - Yang, Yang; Hou, Yuanyuan; Wang, Huiru; Gao, Xiaotong; Wang, Xichang; Li, Jiashu; Teng, Weiping; Shan, Zhongyan (Frontiers in Endocrinology, 2020)
Background: Previous studies indicate the effects of thyroid dysfunction on adverse obstetric outcomes and fetal neurodevelopment, of which the results on gestational anemia are controversial. Here, we evaluated the influence of thyroid dysfunction on gestational anemia via published epidemiological articles and a new prospective study conducted by our team, respectively. Methods: We searched studies on the PubMed, Embase, MEDLINE, and Cochrane databases as of November 2019, and conducted a prospective study in which participants underwent thyroid function and blood routine testing throughout pregnancy. Results: The meta-analysis showed that pregnancies with overt hypothyroidism (OH) (odds ratio [OR] = 3.74, 95% confidence interval [CI] 1.95–7.15) or that were thyroid peroxidase antibody (TPOAb)-positive (OR = 1.97, 95%CI 1.19–3.26) had increased anemia risk, but similar results were not found in pregnancies with subclinical hypothyroidism (SCH) and hyperthyroidism. In the prospective study from our new data, the hypothyroid group had significant reductions in hemoglobin (Hb) (P = 0.048) and increased anemia risk (OR = 6.384, 95%CI 2.498–16.311) during the second half of pregnancy. From the first to second half of pregnancy, the longitudinal reductions in Hb, erythrocyte (RBC), and hematocrit (Hct) levels were significantly increased in hypothyroid group. Conclusions: Our meta-analysis indicates that untreated OH or TPOAb-positive pregnant women have increased risk of anemia. In addition, our new data showed that treated hypothyroidism is also a risk factor for anemia in the second half of pregnancy rather than in the first half. The results may guide strengthening of Hb monitoring in pregnancies with thyroid dysfunction.